Effect of surfactants on mass transfer coefficients in bubble column contactors: an interpretative critical review study - Nekoeian, Sahand; Aghajani, Masoud; Alavi, Seyed Mehdi; Sotoudeh, Fatemeh (Reviews in chemical engineering, 2021)
Since surfactants have been recognized as the most frequently faced contaminants of bubble column-related processes over time, their impact on the mass transfer operation of these columns has become a demanding research interest for two recent decades. Despite the similarities expressing the overall negative and positive influence of these chemicals on mass transfer coefficients and specific interfacial area, respectively, the discrepancies and, sometimes, paradoxical results are still under debate in the literature. To make a more comprehensive recognition of the mentioned subject, the current paper has tried to pave the path by reviewing all the major methods utilized in related research works. Thereafter, an interpretative argumentative comparison of the main findings of relevant studies has also been proposed, enlightening some of the research gaps which can be the potential candidates for future studies.